Collaboration in education - Slater, Judith J.; Ravid, Ruth (Routledge research in education, 2010)
Establishing a needed framework for school/university collaborations, this title explores the elements necessary for sustainable collaboration in order to provide a frame of reference for others doing this work. It also includes analyses of school/university projects in the United States, Asia and Europe.